Synthesis and characterization of manganese triple-decker complexes12. Issue 5 (22nd June 2015) - Heinl, Sebastian; Balázs, Gábor; Bodensteiner, Michael; Scheer, Manfred
Abstract : The synthesis and characterization (experimental and DFT) of sterically encumbered triple-decker complexes of the very rare class of P n ligand complexes of manganese is reported. Abstract : The use of the highly sterically demanding Cp BIG ligand (Cp BIG = C5 (4- n BuC6 H4 )5 ) and white phosphorus (P4 ) enables the synthesis of new P-rich derivatives of the rare P n ligand complexes of manganese. The obtained complexes, [{Cp BIG Mn}2 (μ, η 5:5 -P5 )] (2 ) and [{Cp BIG Mn}2 (μ, η 2:2 -P2 )2 ] (3 ), exhibit the highest number of P atoms in this class of manganese compounds identified by X-ray structure analyses. The EPR spectrum of the 29 VE triple-decker complex2 shows one unpaired electron coupling with two 5/2 spin Mn nuclei.